MODEL PENYEBARAN DEMAM BERDARAH DENGUE UNTUK KOTA PALU - Farida
Dengue is one of the disease a fever caused by the dengue virus which enters the human bloodstream through the bite of a mosquito of the Aedes genus is namely Aedes aegypti. Dengue can appear throughout the year and can attack all age groups. The high spread of dengue vectors generally occurs in urban areas, considering the factors that cause the spread of dengue vectors and viruses, namely mobility and high population density and are important factors because it makes it easier for mosquitoes to infect several people in a short time. As the capital city of Central Sulawesi province with high mobility and population density, Palu city has the highest distribution of dengue cases and is included in the category of dengue endemic areas, and is surrounded by areas with endemicity so that it is an area that has the potential for extraordinary events. Here, we study the spread of dengue virus transmission which is irregular in Palu city only based on weekly data. Host-vector model of the SEIR-SI type was built to simulate the transmission of dengue. Without data on mosquitoes, assuming that mosquito dynamics are much shorter than human dynamics, mosquito dynamics are reduced to their equilibrium point. Then, it is proposed to use Richard’s model to fit the weekly cumulative dengue case data in Palu city so that a solution for each compartment in the host vector SEIR-SI model is obtained. The results showed that the number of weekly active cases obtained from the model had the same trend as the actual weekly infection data in Palu city. In addition, here also the basic and effective reproduction ratio is obtained as the epidemic threshold.